Response to R. Waldman et al.: 'Does IL‐4 inhibition play a role in dupilumab‐associated conjunctivitis?'. (9th February 2020) - Ardeleanu, M.; Shumel, B.; Rossi, A.B.; Graham, N.M.H.
Abstract : Linked Article: Waldman et al . Br J Dermatol 2020; 182:251. Bakker et al . Br J Dermatol 2019; 180:1248–9.